ЛАЗЕРНІ ВИМІРЮВАЛЬНІ СИСТЕМИ З ВОЛОКОННО-ОПТИЧНИМИ СЕНСОРАМИ ДЛЯ КОНТРОЛЮ ЛІНІЙНИХ ПАРАМЕТРІВ МЕХАНІЧНИХ ОБ’ЄКТІВ - Брагинець, І.O.; Масюренко, Ю.О. (Інститут електродинаміки НАН України, Київ, 2021)
A block diagram of a laser measuring system with a fiber-optical sensor for monitoring the air gap between the rotor and stator of a hydrogenerator has been developed and analyzed. The system uses an algorithm for alternating comparison of the investigated and reference light fluxes. This makes it possible to reduce the influence on the measurement result of the gap of the instability of the parameters of individual units and blocks of such a system. The analysis of the main measurement errors, which can affect the result of determining the gap, is carried out. References 16, figure 1.